The Gal/GalNac lectin as a possible acetylcholine receptor in Entamoeba histolytica - Pacheco-Sánchez, Marisol; Martínez-Hernández, Sandra Luz; Muñoz-Ortega, Martín Humberto; Reyes-Martínez, Jesús Alejandro; Ávila-Blanco, Manuel Enrique; Ventura-Juárez, Javier (Frontiers in Cellular and Infection Microbiology, 2023)
Entamoeba histolytica (E. histolytica) is a protozoan responsible for intestinal amebiasis in at least 500 million people per year, although only 10% of those infected show severe symptoms. It is known that E. histolytica captures molecules released during the host immune response through membrane receptors that favor its pathogenetic mechanisms for the establishment of amebic invasion. It has been suggested that E. histolytica interacts with acetylcholine (ACh) through its membrane. This favors the increase of virulence factors and diverse mechanisms carried out by the amoeba to produce damage. The aim of this study is to identify a membrane receptor in E. histolytica trophozoites for ACh. Methods have included identification by colocalization for the ACh and Gal/GalNAc lectin binding site by immunofluorescence, bioinformatic analysis, and quantification of the relative expression of Ras 5 and Rab 7 GTPases by RT-qPCR. The results show that the 150 kDa intermediate subunit of the Gal/GalNAc lectin acts as a possible binding site for ACh. At the same time, this interaction activates GTPases, Ras, and Rab, which involved, proliferation, and rearrangement of the amebic cytoskeleton and vesicular traffic.